(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
Extradural spinal tumors, although generally rare, present significant clinical problems because of their ability to induce spinal cord compression neurological deficits and spinal cord compression. This examines 37 patients who underwent surgical management for extradural spinal tumors in the related hospitals of BSMI from 2022 to 2025 . The considerations include evaluated clinical presentations, diagnostic accuracy, surgical outcomes, andpostoperative Recovery. It has been demonstrated that 78% of patients experienced back pain, while 72% of the tumors were metastatic. Minimally invasive strategies were employed in 42% of patients, leading to reduction.